TFCC Injuries: Meta-Analysis and Comparison of Diagnostic Imaging Modalities - Treiser, Matthew D.; Crawford, Kayva; Iorio, Matthew L. (Journal of Wrist Surgery, 2018)
Background Imaging of the triangular fibrocartilaginous complex (TFCC) remains difficult, as no single imaging modality demonstrates perfect sensitivity and specificity.Purpose This study performs a meta-analysis of multiple previous publications to guide noninvasive imaging selection for the diagnosis of TFCC injuries.Methods A literature search was performed and conducted. Studies were included that compared the diagnostic accuracy of magnetic resonance imaging (MRI), magnetic resonance arthrography (MRA), and computed tomography (CT)/computed tomographic arthrography (CTA) for the evaluation of TFCC injuries. All studies included either arthroscopic or open surgical findings as the “gold standard.” A meta-analysis was performed comparing the diagnostic accuracy of MRA, MRI, and CT for the detection of TFCC injuries.Results Initial search returned 2,568 candidate articles. Studies were then reviewed and narrowed yielding a total of 28 independent studies (20 MRI, 9 MRA, 4 CT/CTA with some studies including multiple modalities) considered in the qualitative data synthesis. Pooling of the raw data in a meta-analysis demonstrated sensitivities of 0.76 (0.72–0.80), 0.78(0.70–0.84), and 0.89 (0.81–0.95) for MRI, MRA, and CT arthrogram, respectively, with specificities of 0.82 (0.77–0.86), 0.85 (0.77–0.92), and 0.89 (0.81–0.95), respectively. Additionally, across all imaging modalities, diagnostic accuracy was highest for central TFCC lesions versus peripheral lesions.Conclusion This study represents the largest meta-analysis to date to compare multiple imaging modalities for the diagnosis of TFCC injuries. Pooled data demonstrated that CTA and MRA had statistically equivalent sensitivity and specificity for the diagnosis of TFCC injuries. Diagnostic accuracy was highest for central TFCC injuries.
Keywords: triangular fibrocartilaginous complex; MRI; computed tomographic arthrography; wrist pain; diagnosis